2019
DOI: 10.1002/da.22947
|View full text |Cite
|
Sign up to set email alerts
|

Associations of PTSD, chronic pain, and their comorbidity on cannabis use disorder: Results from an American nationally representative study

Abstract: Background: Cannabis can be prescribed for posttraumatic stress disorder (PTSD) and chronic pain, and comorbid cannabis use disorder (CUD) can occur in both conditions. Research demonstrates that PTSD and chronic pain commonly co-occur.Methods: Data were acquired from the National Epidemiologic Survey on Alcohol and Related Conditions-III (N = 36,309). Past-year CUD and PTSD were assessed using the Alcohol Use Disorder and Associated Disabilities Interview Schedule-5. Past-year physician-confirmed chronic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 81 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…There is also a disparity between the cannabinoid ratios used in pre-clinical and clinical research that requires further data to address. For example, PTSD pre-clinical studies have focused on the effects of CBD on PTSD symptoms (42)(43)(44)(45)(46)(47)(48) while clinical studies have reported the efficacy of high THC products or simply "cannabis" in treating PTSD (35,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…There is also a disparity between the cannabinoid ratios used in pre-clinical and clinical research that requires further data to address. For example, PTSD pre-clinical studies have focused on the effects of CBD on PTSD symptoms (42)(43)(44)(45)(46)(47)(48) while clinical studies have reported the efficacy of high THC products or simply "cannabis" in treating PTSD (35,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…21 High prevalences of PTSD are observed in cannabis users with CUD seeking treatment 22 and in the general population. 23 A higher prevalence of PTSD was observed in men than in women with CUD in the general population (NESARC 2; DSM-IV), 24 but Kerridge et al…”
Section: Discussionmentioning
confidence: 99%
“…Critical to assessment during the pandemic is a thorough evaluation of the patient's mental health. Symptoms of depression and anxiety are common in persons with persistent pain and SUD (Barry et al, 2017;Bilevicius et al, 2019;Crofford, 2015;Feingold et al, 2017;Søndergård et al, 2018), and can produce substantial barriers to successful treatment of these condition (Oliveira et al, 2019;Worley et al, 2015). Since the beginning of the pandemic, within clinical and general population samples, reported symptoms of anxiety and depression have increased across age and gender, and data continues to accumulate (Cooke et al, 2020;Hawes et al, 2021;Peterson et al, 2021;Salari et al, 2020).…”
Section: Mental Healthmentioning
confidence: 99%